The Effectiviness of Promotional Benefit Towards Buying Intention Moderated By The Brain’s Tendency of Consumers - Evan Stiawan; Tantri Yanuar Rahmat Syah (Journal of Economics, Business, and Accountancy Ventura, 2017)
This research’s goal is to measure the influence of promotional benefit towards buying intention moderated the brain’s tendency of consumers. The object of this research is the consumers whom ever bought a mobile phone. The purpose of this research is to find out the consumer’s buying intention when price discount is higher than premium, the influence of price discount and premium toward buying intention which is moderated by the tendency of consumer’s left and right brain. The data analysis method used is ANOVA One Way and General Linear model (GLM). The result of the research shows that premium is more positively evaluated than price discount which is means the consumer tends to re-buy when premium promotion offered is higher that price discount. The group of consumers that get price discount and right brain tendency tend to have a higher buying intention than the group of consumers that get price discount and left brain tendency, also for the group of consumers that get price discount and right brain tendency tend to have a higher buying intention than the group of consumers that get premium and right brain tendency.